Corrections to “Defending CNN Against FGSM Attacks Using Beta-Based Personalized Activation Functions and Adversarial Training” - Hanen Issaoui; Asma Eladel; Ahmed Zouinkhi; Mourad Zaied; Lazhar Khriji; Sarvar Hussain Nengroo; Sangkeum Lee (IEEE Access)
Presents corrections to the paper, (Corrections to “Defending CNN Against FGSM Attacks Using Beta-Based Personalized Activation Functions and Adversarial Training”).